2006
DOI: 10.1038/sj.npp.1301081
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationships between General (Propofol) Anesthesia and Circadian Time in Rats

Abstract: Several common postdischarge symptoms, such as sleep disorders, headache, drowsiness or general malaise, evoke disturbances of circadian rhythms due to jet lag (ie crossing time zones) or shift work rotation. Considering that general anesthesia is associated with numerous effects on the central nervous system, we hypothesized that it may also act on the circadian timing system. We first determined the effects of the circadian timing on general anesthesia. We observed that identical doses of propofol showed mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 37 publications
(45 reference statements)
2
32
1
5
Order By: Relevance
“…In contrast to Cheeseman et al (9) and Challet et al (10), isoflurane administration caused suppression of circadian gene expression but did not cause a shift in circadian pattern in investigated tissues. Cheeseman et al (9) kept animals in a DD cycle after anaesthesia administration, and they found a phase shift in circadian gene expression.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In contrast to Cheeseman et al (9) and Challet et al (10), isoflurane administration caused suppression of circadian gene expression but did not cause a shift in circadian pattern in investigated tissues. Cheeseman et al (9) kept animals in a DD cycle after anaesthesia administration, and they found a phase shift in circadian gene expression.…”
Section: Discussioncontrasting
confidence: 49%
“…They concluded that general anaesthesia during the day caused a persistent and marked shift of the clock, effectively inducing 'jet lag' and causing impaired time perception. Challet et al (10) reported that 30 min propofol administration causes a one-hour time shift in circadian rhythms (activity and temperature) in rats which were kept in a darkdark (DD) cycle during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, rats receiving an i.p. injection of propofol at night-time sleep for a shorter duration compared with animals tested with propofol during the daytime, which could possibly be due to faster propofol metabolism (Challet et al, 2007). Thus, variation in brain CYP2B levels may introduce noise or error into rat studies, if the drugs tested are CYP2B substrates and the experiments vary in the time of day.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, some anesthetics can affect behavioral and physiological rhythms in rodents. Whereas the benzodiazepine midazolam and the opiate fentanyl can cause phase advances and delays in locomotor activity depending on the time of administration (25), the anesthetic propofol induces only phase advances (26). Moreover, the inhalational anesthetic sevoflurane has been shown to cause phase delays in activity of ∼1 h when administered during the subjective day (27).…”
Section: Discussionmentioning
confidence: 99%